Cultural Experience, Tourist Emotion And Revisit Intention In Rammang-Rammang Tourism Village, Indonesia - Ilma Wulansari Hasdiansa; Sitti Hasbiah (International Journal of Education Management and Religion, 2026)
: Cultural tourism destinations increasingly need to provide meaningful and emotionally engaging experiences to encourage tourists’ future behavioral intentions. However, limited studies have examined how cultural experiences influence revisit intention through tourist emotion in community-based tourism villages, particularly in Indonesia. This study aims to investigate the effect of cultural experience on revisit intention through tourist emotion among visitors of Rammang-Rammang Tourism Village, Indonesia. A quantitative survey approach was employed involving 115 tourists who had visited the destination within the last two years. Data were analyzed using Structural Equation Modeling (SEM) with AMOS 22.0. The findings indicate that cultural experience positively and significantly affects tourist emotion (β = 0.741, p < 0.001) and revisit intention (β = 0.286, p < 0.01). Tourist emotion also positively influences revisit intention (β = 0.554, p < 0.001) and significantly mediates the relationship between cultural experience and revisit intention. The novelty of this study lies in examining the mediating role of tourist emotion within a community-based cultural tourism village context. The findings suggest that sensory, emotional, participatory, and reflective cultural experiences strengthen tourists’ emotional attachment and encourage revisit behavior. These results contribute to cultural tourism literature and provide practical guidance for destination managers in designing more experiential and emotionally meaningful tourism programs.